Una elección difícil? Comparación de los ingresos fiscales que recaudarán los países en vías de desarrollo a partir de los regímenes del Monto A y del Artículo 12B de la Convención Modelo de las Naciones Unidas - Vladimir Starkov; Alexis Jin (South Centre, 2022)
In this research paper, we attempt to estimate the tax revenues to be gained (or lost) by the South Centre and African Union's Member States under the Amount A and Article 12B regimes. Our analysis relied on sources of information available to private sector researchers but did not involve review of any information that taxpayers provide to tax authorities. Our research demonstrates that the comparative revenue effects of the Amount A and Article 12B taxation regimes largely depend on (a) design details of the Article 12B regime, (b) whether the country hosts headquarters of MNEs that may be in scope of Amount A or Article 12B taxation, and (c) what relief from double taxation, if any, the country will grant to domestic taxpayers subject to taxation under either the Amount A or Article 12B regimes.
Keywords: 300; African Union (AU); Amount A; Article 12B; Automated Digital Services (ADS); Base Erosion and Profit Shifting Project (BEPS); Coalition for Dialogue on Africa (CODA); Digital Economy; Digital Tax; Digital Taxation; Double Taxation; Global Tax; Global Taxation; Inclusive Framework; International Tax; International Tax Cooperation; International Taxation; Multinational Enterprises (MNEs); Organisation for Economic Co-operation and Development (OECD); Pillar One; South Centre Member States; Tax; Tax Cooperation; Tax Law; Tax Policy; Tax Reform; Taxation; Taxation in Developing Countries; Two Pillar Solution; UN Model Double Taxation Convention; United Nations Committee of Experts on International Cooperation in Tax Matters (UNTC)